2023
DOI: 10.3389/fsufs.2023.1045592
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic fertilizers produced from fish pond sediment on growth performances and yield of Malabar and Amaranthus vegetables

Abstract: The increasing intensification of aquaculture production requires the development of strategies to reduce its environmental impacts such as the pollution caused by the discharge of nutrient-rich sediments into local water bodies. This research was undertaken to investigate and evaluate the effect of using organic fertilizers produced from the pond sludge of freshwater snakehead fish (Channa striata) composted with organic amendments of peanut shells and coir fiber on growth performance indices and yields of Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The experiments were carried out in cultivation bags filled with the substrate (TurfaFertil), composed of carbonized rice husk, limestone, turf, and earthworm humus with the following chemical characteristics: N = 7.5 g kg −1 ; P = 5.01 g kg −1 ; K + = 4.42 g kg −1 . The cultivation bag was 1.5 m long and 0.5 m wide and had a total volume of 55 dm 3 . Data for minimum, average, and maximum temperature and rainfall are given in Tables S1 and S2 for Londrina and Bandeirantes, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments were carried out in cultivation bags filled with the substrate (TurfaFertil), composed of carbonized rice husk, limestone, turf, and earthworm humus with the following chemical characteristics: N = 7.5 g kg −1 ; P = 5.01 g kg −1 ; K + = 4.42 g kg −1 . The cultivation bag was 1.5 m long and 0.5 m wide and had a total volume of 55 dm 3 . Data for minimum, average, and maximum temperature and rainfall are given in Tables S1 and S2 for Londrina and Bandeirantes, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that organic fertilization and amendment have a positive impact on vegetable growth [3][4][5][6][7]. One of the options is the use of organic matter with a controlled process of fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…By incorporating these factors into the geometric design of the pond, it is possible to create a more stimulating and comfortable environment for the fish 7 . The MGD can also help to improve fish growth performance 8 . This is because fish that are stressed or uncomfortable are less likely to eat or grow as quickly; creating a more natural and stimulating environment for the fish can reduce stress and improve their growth performance 9 .…”
Section: Introductionmentioning
confidence: 99%